2022
DOI: 10.1161/jaha.121.023713
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Venoarterial Extracorporeal Membrane Oxygenation Plus Intra‐Aortic Balloon Pumping for Treatment of Acute Myocardial Infarction Complicated by Cardiogenic Shock

Abstract: Background Clinical outcomes of acute myocardial infarction complicated by cardiogenic shock remain poor with high in‐hospital mortality. Veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) has been widely used for patients with acute myocardial infarction complicated by cardiogenic shock refractory to conservative therapy, which is likely fatal without mechanical circulatory support. However, whether additional intra‐aortic balloon pumping (IABP) use during VA‐ECMO support improves clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…[36] Recent study showed that ECMO, in addition to IABP support with proper management of device-related complications, may lead to improved clinical outcomes of CS in patients with MI (HR 0.30, 95% CI, 0.25-0.37), similar results as shown in the present study. [37] The strength of this study was that long-term mortality included short-term mortality with VA-ECMO + IABP support, which we provided with adjusted incidence rates using various statistical methods. A recent systematic review showed that most studies regarding the clinical outcomes of ECMO support only reported crude incidence and indicated the harmful effects of ECMO during the early stage of MI-CS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36] Recent study showed that ECMO, in addition to IABP support with proper management of device-related complications, may lead to improved clinical outcomes of CS in patients with MI (HR 0.30, 95% CI, 0.25-0.37), similar results as shown in the present study. [37] The strength of this study was that long-term mortality included short-term mortality with VA-ECMO + IABP support, which we provided with adjusted incidence rates using various statistical methods. A recent systematic review showed that most studies regarding the clinical outcomes of ECMO support only reported crude incidence and indicated the harmful effects of ECMO during the early stage of MI-CS.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Recent study showed that ECMO, in addition to IABP support with proper management of device-related complications, may lead to improved clinical outcomes of CS in patients with MI (HR 0.30, 95% CI, 0.25–0.37), similar results as shown in the present study. [37]…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported the decision for additional IABP treatment was made by the physician in charge (28,33), two studies reported that an IABP was routinely implanted in absence of any contra indication (21,30) and one study reported that an additional IABP was implanted in case the arterial pulse wave disappeared after using VA-ECMO support (22). Four studies reported the 30-day/in-hospital mortality (23)(24)(25)28) and eight studies the in-hospital mortality (21,22,26,(30)(31)(32)(33). Overall mortality was 75.1% (n = 3802) and 85.6% (n = 973) in the VA-ECMO and 72% (n = 2829) in the VA-ECMO + IABP group.…”
Section: Reasons For Iabp Treatmentmentioning
confidence: 99%
“…Cardiogenic shock (CGS), one of the complications of AMI, is one of the prime reasons for death in AMI patients [ 6 ]. However, at present, the clinical effect of AMI complicated with CGS leaves much to be desired, urgently demanding effective measures that can be taken to lower the incidence of complications to extend patient survival [ 7 ]. This study aims at finding a more suitable nursing method for senile AMI patients from the perspective of nursing care.…”
Section: Introductionmentioning
confidence: 99%